Is anything really new in mechatronics education?. - Craig, K. (IEEE Robotics and automation magazine)
Yes, there is something new in the way mechanical engineers are expected to design and in the way professors must now teach design. To illustrate how one institution is helping mechanical engineers to become mechatronics engineers, the article describes the undergraduate program in mechatronics at Rensselaer Polytechnic Institute, and in particular, the integration of the theory covered in lectures with the laboratory exercises. The hardware systems used in both courses are described. Also discussed are observations from conducting professional training in mechatronics both in industry and for the ASME Professional Development Program